WISATA DAN SENI PERTUNJUKAN BETAWI DENGAN KONSEP BETAWI PESISIR - Muhammad Ilham Sudrajat; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Kelurahan Marunda was once a place which known for its Betawi culture in Jakarta. The existence of Museum Si Pitung in the area reflected the Betawi culture, sourced from its folklores (of Betawi culture). However in present day, Kelurahan Marunda is now more one of Jakarta’s Industrial Area. As in writer’s opinion, it is important to keep Kelurahan Marunda famous for its Betawi culture, in order to keep the Betawi identity of Kelurahan Marunda itself. The site the writer chose is near from Pantai Marunda, known locally as ‘Tempat Wisata/Recreational Place’, which until now still frequently visited by publics. Considering the site of the writer chose, therefore the writer looks up to the theory of Biophilic Design. The writer propose to build an area with Betawi Culture Concept in Coastof Kelurahan Marunda with 3 main activity programs as: The traditional art conservation activities, for example dancing arts, musics, theatres and matrial arts. Next memorabilia conservation activities, putting in bold of water recreation conservation activities in the Coast of Marunda.Also there are activities which contain Betawi Culture’s image conservation, in this will be bolding the culinary and accessories sectors out. The above-proposed Betawi Culture tourism area is definitely important for Marunda Area, because it will also creates working opportunities for the locals, and the most important once more is to keep the Betawi identity in Marunda itself. Keywords:  Betawi Culture Art; Betawi Coastal; Eco-Tourism Principles AbstrakKelurahan Marunda merupakan tempat yang kental terhadap budaya Betawi di Jakarta. Adanya bangunan Museum Si Pitung di kawasan Marunda melambangkan adanya cerita di Marunda yang mengacu pada cerita-cerita budaya Betawi. Namun di masa sekarang, Marunda menjadi bagian kawasan industri di Jakarta. Saya berpendapat bahwa sangat pentinglah adanya suatu kawasan di Marunda yang masih berpegang teguh pada kebudayaan Betawi, untuk mempertahankan identitas asli kawasan Marunda.  Tapak yang terpilih berada di Pantai Marunda, tapak ini merupakan tempat wisata di Marunda yang masih kerap dikunjungi oleh warga. Dengan teori perancangan biofilik desain. Maka dari itu, penulis mengusulkan untuk membangun sebuah kawasan dengan konsep Betawi Pesisir di wilayah Marunda dengan menentukan 3 program aktivitas utama dalam kawasan dan juga menentukan zonasi pada tapak antara lain adalah. Aktivitas pelestarian kesenian, seperti kesenian tari, musik, teater, dan juga pencak silat. Ada juga aktivitas pelestarian memoribilia, yang di dalamnya merupakan zona yang berfokus pada pelestarian rekreasi air, dimana adanya kegiatan yang berkaitan dengan penduduk Betawi Pesisir di kawasan Marunda. Dan yang terakhir adalah aktivitas pelestarian citra, dalam zona ini lebih mengacu kepada pelestarian kuliner dan aksesoris.  Proyek kawasan pariwisata kebudayaan Betawi Pesisir ini sangatlah baik untuk wilayah Marunda. Karena dapat menciptakan lapangan pekerjaan, dan juga mempertahankan identitas Betawi Pesisir di Marunda.